Interference of gadolinium dechelated from MR contrast agents by calcium signaling in neuronal cells of GnRH - Baykara, Murat; Ozcan, Mete; Bilgen, Mehmet; Kelestimur, Haluk (Wiley, 2021)
Contrast agents (CAs) used in magnetic resonance imaging (MRI) are produced by chelating the metal gadolinium (Gd) with organic ligand molecules to form stable complexes. But, Gd(3+)may dissociate from the CAs and subsequently might become toxic to its environment. Besides toxicity, it might inhibit calcium channels on cell membranes and this action could be detrimental to the cells governing biological development. The aim of this study was to investigate the interference of Gd3+ dechelated from the CAs by calcium signaling in the neuronal cells of gonadotropin-releasing hormone (GnRH), regulating puberty, and sexual development. The study used the mouse GT1-7 cell line as a model system, and Fura-2 based calcium imaging for detecting the interruption of intracellular calcium transport by the extracellular presence of Gd3+ as released from the CAs; gadodiamide and gadoterate meglumine, when the cells were stimulated in vitro culture by exposure to melatonin.The CA gadoterate meglumine interfered minimally with the calcium signaling, and thus its use is preferable in standard MRI exams. The release of Gd3+ from gadodiamide was significant and becomes of great concern as it may impact the neurophysiology of the neuronal cells in general, and gonadotropin production in particular, even in normal patients without nephrogenic systemic fibrosis. The toxicity induced by the influx of dechelated Gd3+ in the neurons of GnRH would have significant implications for puberty and reproductive functions.
Keywords: calcium signaling; contrast agent; gadolinium; gonadotropin-releasing hormone; GT1-7 cell line; magnetic resonance imaging